PENGARUH KEMANDIRIAN BELAJAR SISWA TERHADAP PRESTASI BELAJAR PESERTA DIDIK SMP NEGERI 120 JAKARTA - Intan Kusuma Dewi (Yayasan Akrab Pekanbaru, 2018)
The purpose of this research is to know how big influence student independence to student achievement of SMP Negeri 120 Jakarta. Learning achievement is the result of learning that can be achieved after through the process of teaching and learning activities. Learning achievement can be demonstrated through the value provided by an educator of the number of fields of study that have been studied by learners. Each learning activity would always expect to produce maximum learning. Data taken through survey and research using survey research method, ex post facto, experiment, naturalistic, policy research (Research policy), action research, evaluation and history. The result of this research is the result of coefficient of determination analysis (rÂ²) variable of learning independence (x2) to learning achievement (Y) is 0,474. This means that 47,4% of variation that happened on learning achievement variable (Y) can be predicted by the variable of learning independence (x2), or in other words the variable of learning independence as predicator variable can be relied on to predict the variable of learning achievement of SMP Negeri 120 Jakarta as much as 52.6%. Keywords: Student Learning